2021
DOI: 10.1016/j.arth.2020.09.045
|View full text |Cite
|
Sign up to set email alerts
|

The Anatomical Course of the Superior Gluteal Nerve With Regard to the Direct Anterior Approach for Primary and Revision Total Hip Arthroplasty

Abstract: Background: During primary and revision total hip arthroplasty (THA) lesions of the superior gluteal nerve (SGN) can substantially compromise patient outcome. For the primary direct anterior approach (DAA) and its proximal approach extensions, especially the muscular branch entering the tensor fasciae latae (TFL) muscle is at risk. SGN lesions can result in fatty atrophy and functional loss of the TFL. Therefore, the course and branching pattern of the SGN were examined and related to the DAA and its proximal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 30 publications
1
15
0
Order By: Relevance
“…To obtain that field of view, about 40 mm from the apex of the greater trochanter must be developed proximally between the Gmed and TFL. This is within the red zone proposed by Vasco [11], who considered that the terminal branches of the descending SGN branches running to the TFL are more likely to be damaged in the ALS THA approach. Unis et al [12] observed TFL atrophy in 61% of 16 patients in 26 THAs using a modified anterolateral approach.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…To obtain that field of view, about 40 mm from the apex of the greater trochanter must be developed proximally between the Gmed and TFL. This is within the red zone proposed by Vasco [11], who considered that the terminal branches of the descending SGN branches running to the TFL are more likely to be damaged in the ALS THA approach. Unis et al [12] observed TFL atrophy in 61% of 16 patients in 26 THAs using a modified anterolateral approach.…”
Section: Discussionsupporting
confidence: 64%
“…Several travel patterns of the descending branches of the superior gluteal nerve have been described [10]. In a study by Vasco et al [11], the average distance to the greater trochanter at the site where the peripheral motor branches of the SGN entered the TFL was 72.5 mm, with a large range of 40-110 mm. They also observed a considerable variation in the branching pattern of nerves before entering the TFL and defined the "red zone" as the region where 75% of the SGN terminal branches entered the TFL.…”
Section: Discussionmentioning
confidence: 99%
“…The nerve emerges from the gluteal muscles and courses inferiorly about 3 cm under the TFL fascia freely, as seen in our study. The second and final study on this subject in the literature to date is that of Starke et al 34 For both the DAA and ALA, it was emphasised that surgery performed close to the GT in the region between the ASIS and GT is suitable for preserving the TFL branches of the nerve. Their suggestions for protecting TFL branches are in line with the conclusions of our study.…”
Section: Discussionmentioning
confidence: 99%
“…In studies by Grob et al (2015) and Starke et al (2021), THA through the DAA was successful without side effects, but muscle atrophy occurred as a postoperative complication. Researchers have since used various methods to identify injuries at the terminal branch of the inferior SGN as the cause of muscle atrophy (Takada et al, 2018;Vajapey et al, 2020).…”
mentioning
confidence: 97%
“…There is also a high possibility of intraoperative damage at the site where the SGN enters at the surface of the TFL. Starke et al (2021) reported that the branch of the SGN entering the TFL could be damaged during DAA.…”
mentioning
confidence: 99%